Artemisia annua‐sublingual immunotherapy for seasonal allergic rhinitis: A randomized controlled trial. Issue 8 (23rd February 2020) - Lou, Hongfei; Huang, Yanran; Ouyang, Yuhui; Zhang, Yuan; Xi, Lin; Chu, Xiaohan; Wang, Yang; Wang, Chengshuo; Zhang, Luo
Abstract: Background: Artemisia annua is an important autumnal pollen allergen for seasonal allergic rhinitis (SAR) in northern China. To date, no study has investigated allergen immunotherapy with A annua . We aimed to investigate the efficacy and mechanisms underlying A annua ‐sublingual immunotherapy (SLIT). Methods: This was a randomized, double‐blind, placebo‐controlled phase III clinical trial involving 71 SAR patients, randomized to SLIT with A annua extract (n = 47) or placebo (n = 24) for 32 weeks. Total nasal symptom score (TNSS; primary clinical end point) was evaluated at baseline (peak pollen phase (PPP) in the previous year), initiation of A annua ‐SLIT, 1st PPP during SLIT, end of SLIT and 2nd PPP during follow‐up. Blood samples and nasal secretions were collected at beginning and after SLIT for assessment of T cells and inflammatory mediators. Safety was assessed according to adverse events (AEs) reported. Results: Artemisia annua ‐SLIT significantly reduced TNSS to a greater level from baseline (from 9.45 ± 1.68 to 6.16 ± 2.27) than placebo (from 9.29 ± 2.09 to 9.05 ± 2.40) at the 1st PPP ( P < .001) and sustained the improvement in symptoms throughout to the 2nd PPP. Preseasonal A annua ‐SLIT for 16 weeks significantly decreased Th2 cells, increased nTreg and Tr1 cells in blood; and increased cystatin 1 (CST1) in nasal secretion after 16 and 32 weeks compared with pretreatment. Overall, 17/47 patients experienced mild local AEs and 2 patients mild systemic AEs, after A annua ‐SLIT. Conclusion: Artemisia annua ‐SLIT is an efficacious and safe treatment in patients with A annua SAR. Abstract : This randomized, double‐blind, placebo‐controlled phase III clinical trial demonstrates the efficacy and favourable safety profile of the 32‐week SLIT with Artemisia annua in patients with seasonal allergic rhinitis. Artemisia annua ‐SLIT significantly reduces total nasal symptom score at the 1st and 2nd PPP compared with placebo. Preseasonal Artemisia annua ‐SLIT significantly decreases Th2 cells, increases nTreg and Tr1 cells in blood and increases CST1 in nasal secretion.